CONCEPTS OF GENETICS AND THE USE OF INTERACTIVE METHODS IN SOLVING PROBLEMS OF GENETICS (Conferencea, 2022)
This article is written for schoolchildren on the use of interactive methods in the independent study of genetic concepts and methods of solving genetic problems in biology lessons.